Soluble form of the receptor for advanced glycation end-products attenuates inflammatory pathogenesis in a rat model of lipopolysaccharide-induced lung injury - Yasuhisa Izushi; Kiyoshi Teshigawara; Keyue Liu; Dengli Wang; Hidenori Wake; Katsuyoshi Takata; Tadashi Yoshino; Hideo Kohka Takahashi; Shuji Mori; Masahiro Nishibori (Elsevier, 2016)
Acute respiratory distress syndrome (ARDS) is a severe respiratory failure caused by acute lung inflammation. Recently, the receptor for advanced glycation end-products (RAGE) has attracted attention in the lung inflammatory response. However, the function of soluble form of RAGE (sRAGE), which is composed of an extracellular domain of RAGE, in ARDS remains elusive. Therefore, we investigated the dynamics of pulmonary sRAGE and the effects of exogenous recombinant human sRAGE (rsRAGE) under intratracheal lipopolysaccharide (LPS)-induced lung inflammation. Our result revealed that RAGE was highly expressed on the alveolar type I epithelial cells in the healthy rat lung including sRAGE isoform sized 45 kDa. Under LPS-induced injured lung, the release of sRAGE into the alveolar space was increased, whereas the expression of RAGE was decreased with alveolar disruption. Treatment of the injured lung with rsRAGE significantly suppressed the lung edema, the neutrophils infiltration, the release of high mobility group box-1 (HMGB1), and the expressions of TNF-α, IL-1β and iNOS. These results suggest that the alveolar release of sRAGE may play a protective role against HMGB1 as well as exogenous pathogen-associated molecular patterns. Supplementary therapy with sRAGE may be an effective therapeutic strategy for ARDS.